DIABETES MELLITUS TYPE II AND GRADE I HYPERTENSION ACCOMPANIED OBESITY ON 75 YEARS OLD WOMAN WITHOUT - Aziztama, Rezandi (Jurnal Agromedicine Unila: Jurnal Kesehatan dan Agromedicine, 2014)
Hypertension is often associated with risk of diabetes and other diseases. The prevalence of both conditions is quite high and tends to increase from year to year. Hypertension can lead to complications of a stroke, heart and kidney failure, can even cause sudden death, as well as with diabetes. This is often caused due to an unfavorable lifestyle and psychosocial stress, mild daily activity and completed with varieties of psychosocial problems that are not easily to be resolved. Ny. IN , 75 years old , with chief complaint of pain in nape of neck since 2 weeks ago. The complaints was Intermittent, and become heaver when the patient have less of rest. The patient often feels unsteady, but improves with rest. Patients already taking over the counter medicine, but the symptoms did not recover, because of that the patient went to the health center. Patient had a history of diabetes since 2008. Patient rarely control her treatment, patient seek treatment if only there was a complaint. The patient also had a history of hypertension, but patients do not regularly take medicine and the patient does not routinely control to health centers. From physical examination, patient seems in mild pain; temperature was 36,7oC; blood pressure was 150/90 mmHg; pulse rate was 80x/min; respiration rate was 22x/min; weight 61 kg; height 155 cm; nutritional status was obesity grade 1 (BMI: 25.39). Laboratory tests found blood sugar at any time test 200 gr/dl. Therefore, the role of community and family is helpful in completion of clinical problems. Clinical problems and complex changes in behavior can not be resolved within 4 weeks. Required patient desirability to change the behavior, and also need support of the family. It should be integrated based on family risk factors that theoretically therapy with family support might work. [J Agromed Unila 2014; 1(2):174-179] Keywords: diabetes mellitus, hypertension, risk factor